Risk of grade 3-4 diarrhea and mucositis in colorectal cancer patients receiving anti-EGFR monoclonal antibodies regimens: A meta-analysis of 18 randomized controlled clinical trials. Issue 2 (November 2015) - Miroddi, Marco; Sterrantino, Carmelo; Simonelli, Ilaria; Ciminata, Giorgio; Phillips, Robert S.; Calapai, Gioacchino
Highlights We reviewed 18 clinical trials enroling 13, 958 patients with colorectal cancer. We compared standard therapies with those therapies plus cetuximab or panitumumab. We assessed risk of severe diarrhea and mucositis in intervention and control groups. We found an increased risk in patients receiving Cetuximab or panitumumab. Adopting risk reduction strategies to limit impact of these AEs is needed.